(untitled) (Environment & Health, 2021)
Objective: We performed the eco-hygienic assessment of electromagnetic fields as an environmental factor under modern conditions. Materials and methods: We determined a range of issues on the significance of electromagnetic fields of various frequencies and intensities in human vital activity on the basis of the analysis of scientific literature. Results and discussion: Taking into account the further development of the national economy of the country, safety and protection of the population from the effects of electromagnetic fields both in industry and everyday life remain one of the urgent problems, taking into consideration that their biological effect on the human organism is very complex and has not been completely studied. In this regard, special attention should be paid to the use of hand-held telephones and computers which are used by the people of different age, gender and physiological state of the organism. Therefore, the existing protection measures against the negative effect of EMF require further improvement and refinement. Conclusions: Protection of the population from the adverse effects of electromagnetic radiation of various frequencies and intensities has been and remains an urgent eco-hygienic problem of mankind, and medical workers, engineers, biologists, ecologists and other specialists should participate in its solution.